(untitled) (Eurasian Journal of Media and Communications, 2024)
The current research aims to identify the role of public relations in crisis management within universities - Al-Mustansiriya University, College of Administration and Economics, as a model. This study represents an effective contribution to understanding the role of public relations in crisis management within universities, with a focus on the College of Administration and Economics at Al-Mustansiriya University as a model. The study aims to analyze the efficiency of public relations strategies in dealing with urgent challenges that may affect the university context. The study uses a survey approach and includes a sample representing the College of Administration and Economics, as it evaluates the public relations plans and strategies adopted for crisis management. Analysis of previous experiences at the college provides an opportunity to understand the challenges it faced and how these experiences can be used to enhance the college’s readiness to face future challenges. The study is expected to contribute to identifying the strengths and weaknesses of the role of public relations within universities, which contributes to developing effective crisis management strategies. More broadly, the findings and recommendations presented by the research can provide a valuable reference for other universities in enhancing the effectiveness of their efforts in dealing with emerging challenges in the context of higher education